Development Of A Nanoemulsion-Based Sheet Mask Containing Soybean Oil And Turmeric Oil To Reduce Stretch Marks In Postpartum Women - Wijayanti, Dianita; Widyawati, Melyana Nurul; Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background: Stretch marks are a common problem in 90% of postpartum women, which can lower their self-confidence. Soybean oil and turmeric oil have the potential to regenerate the skin due to their isoflavon and curcumin content. Nanoemulsion is expected to increase the effectiveness of active ingredient absorption into the skin. Objective: To analyze the formulation, physicochemical characteristics, stability, and effectiveness of a nanoemulsion sheet mask containing soybean and turmeric oil for concealing stretch marks in postpartum women. Research Method: This type of research is R&D, and Quasi Eksperimental Pre-Posttest With Control Group Design. A total of 32 postpartum women were divided into two groups, intervention group (n=16, soybean oil 5% and turmeric oil 5% nanoemulsion sheet mask) and control group (n=16, VCO sheet mask). The treatment was administered twice a week for 4 weeks. Stretch marks were measured using the Davey Score and analyzed using the Independent T-Test. Results: The nanoemulsion was made using an ultraturrax and produced a stable and safe product with a particle size of 94.75-163.7 nm, pH 6.5-7.1, and did not cause irritation. The average stretch Marks score decreased in both groups (Intervention group from 6.38 to 5.13; control group from 5.38 to 4.56). Statistikal analysis showed no significant difference in efficacy between the two treatments (p > 0.05). The difference in score reduction in the nanoemulsion group was 1.25 higher than in the VCO group. Conclusion: The nanoemulsion sheet mask was successfully formulated, stable, and safe for the skin. The use of this sheet mask can reduce stretch Marks scores, and its effectiveness is not significantly different from that of the VCO group.